Subclinical growth of an arteriovenous fistula associated with renal biopsy: a case report. Issue 1 (December 2016) - Murakami, Takuya; Takeda, Shin-ichi; Kanazawa, Hidenori; Ugajin, Atsushi; Kijima, Shigeyoshi; Nakamura, Hiroyasu; Imai, Toshimi; Sugase, Taro; Horikoshi, Ryoko; Kobayashi, Takahisa; Akimoto, Tetsu; Saito, Osamu; et al.
Abstract Background Renal biopsy is not free from complications and patients who undergo this procedure are usually hospitalized to receive intensive care for several days after biopsy. In contrast, after this period, routine follow-up to detect biopsy-associated complications is rarely scheduled, unless the patient develops a clinical manifestation. We describe a case of marked enlargement of arteriovenous fistula in the kidney that occurred many years after renal biopsy. In contrast to the previous cases requiring interventional radiology, our patient showed subclinical growth of fistula over about nine years. Case presentation A 24-year-old man with a history of percutaneous renal biopsy was hospitalized for interventional radiology. Gross hematuria emerged shortly after biopsy, but completely disappeared with administration of hemostatic agents and bed rest. Subsequently, the patient had few symptoms for many years. A giant fistula (a gourd-shaped mass, size 26 × 22 and 12 × 11 mm) was unexpectedly detected by ultrasonography performed for examination of an unrelated disorder (slight elevation of serum transaminase) at 9 years after the original biopsy. The fistula was successfully treated with radiological intervention. Thus, subclinical development of complications associated with renal biopsy should be considered, even in an uneventful course. Conclusions This case provides a platform to discuss the importance of long-term follow-up of patients after renal biopsy despite of its difficulty.